PENGGUNAAN METODE EKSTRAKSI PADA PROSES PENGOLAHAN DEDAK PADI (RICE BRAN) MENJADI MINYAK PANGAN - Lince Muis (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
Rice bran is byproduct result  from process of grinder shell of rice become the rice, what is only used as livestock feed. Rice bran basically rich of substance of obstetrical nutrient of fat about 14%.  Rice bran can be developed permanent upon which in making of food oil. therefore done by a research. The research  use the method extraction use the hexane as a solvent to know the influence of time of extraction and difference of size measure of bran to yielded oil rate. This research is conducted by three types of size measure of bran that is 0,2 mm, 0,6 mm and 1 mm and variation of of time ekstraksi 4,5, and 6 clock.  Early stage of research is preparation of raw material in the form of rice bran sieved and deliberated, hereinafter extraction, result of from extraction have to distillation to dissociate the pelarut from oil. Bran oil which obtain; get is later; then analysed by a rate, sour of free fat and peroxide number. Obtained a bran oil of at size measure of bran 0,2 mm and time extraction 6 clock with the oil rate 18,43 %, acid contents free fat 0,9 % and peroxide number 0,9 %.Key Word : rice bran, hexane, distillation, extraction,  time, bran